Promoting Hand and Foot Care Among Vegetable Farmers to Prevent Occupational Diseases: Upaya Promotif Perawatan Tangan Dan Kaki Pada Petani Sayur Dalam Mencegah Penyakit Akibat Pekerjaan (JURNAL UNEJ, 2024)
Indonesia is an agricultural country where most of the population's livelihood is in the agricultural sector. Agriculture can pose a wide spectrum of health hazard risks. Farmers need a very high level of hygiene awareness and good personal hygiene, especially in maintaining the cleanliness of the skin and nails. Service activities are carried out using a health promotion/health counseling approach with lectures, demonstrations, and question-and-answer methods on how to care for hands and feet vegetable farmers. The media used is x-banner. The media contains a description of the dangers for vegetable farmers and ways to care for hands and feet in vegetable farmers. The time allocation is 60 minutes. Health promotion with lecture methods, demonstrations, and the use of x-banner media on vegetable farmers is an effort that can be used to increase the absorption of information from extension workers. It is hoped that this health counseling can be carried out on an ongoing basis so that vegetable farmers can change their behavior and avoid the dangers of occupational diseases transmitted through hands and feet.